Meningkatkan Minat Membaca Anak Anggota Sanggar Pelita Melalui Metode Belajar Sambil Bermain - Yelsa Katrina Saragih; Randa Putra Kasea Sinaga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Interest in reading has a big influence on children's success so it needs to be grown from an early age. Parents must get used to and direct their children regularly to read a lot for themselves, then in the child will grow the habit of becoming an early reader who has a natural interest in reading. For this reason, this interest in reading needs to be instilled in children from an early age. Reading is considered as one of the success of a child in learning. Increasing interest in reading is done from an early age to provide children with real experiences. In increasing interest in reading, a method that can be used is needed to increase children's interest in reading. The method chosen is the method of learning while playing. The purpose of this study is to increase children's interest in reading by using the learning while playing method. This research is an experimental and observational research. The population in this study were all children of Sanggar Pelita members on Jl. Bangun Sari, Kel. Kedai Durian, Kec. Medan Johor, Medan City with 15 children as the sample in the age group of 6-13 years. The results showed that the students' interest in reading after the application of the learning while playing method was better than before. With these results, it is concluded that the learning while playing method is effective in increasing students' reading interest in children aged 6-13 years.